Optimizing Creative Thinking Skills Through STEM-PJBL: The Impact of Digital Modules - Rosita Dwi Ferdiani (Universitas Pendidikan Ganesha, 2025)
Creative thinking is one of the cognitive skills essential for facing the challenges of Society 5.0, and education plays a crucial role in fostering this ability. Learning media are needed to enhance creative thinking, including digital modules within STEM Project-Based Learning (STEM PjBL). This study focuses on the impact of digital modules with STEM PjBL on students’ creative thinking. The research employed a Mixed Exploratory Design Method, combining qualitative and quantitative approaches sequentially, beginning with qualitative analysis followed by quantitative methods. Instruments used in the study included pre-test and post-test questions, as well as the digital module for STEM PjBL. The study involved 297 junior high school students, specifically classes VIII A and VIII B, with VIII A serving as the experimental group implementing the digital STEM PjBL module and VIII B as the control group without module implementation. Creative thinking indicators were fluency, flexibility, and originality. The novel contributions of this research are twofold: (1) the implementation of digital modules in STEM PjBL positively affects students’ creative thinking, and (2) differences in creative thinking across the aspects of originality, fluency, and flexibility are observed among individual participants while completing project tasks.